Automated vending machine system - Mohammad Ali, Mohd. Hasyim (2007)
Nowadays, sales using the vending machines are increasingly popular. This business can be ventured by almost anyone; i.e individuals, private organizations or governmental bodies. In the market today, there are different varieties of vending machine that sells a whole variety of food and beverages. Currently there's a new vending machine which is hitting into our market; Prepaid Vending Machines. These vending machines have long been introduced in countries like the United State and United Kingdom but only recently in our country,making it a great potential that is yet to be tapped. One advantage of this machine is that it will be equipped with an AVMS system and a monitor screen,unlike the ones that are currently available on the market today. The AVMS system would consists some of modules which are : an accounting module, inventory module, machine positioning information module, maintenance module, report regeneration module, product sales performance module, margin calculation module, graphical analyser device module and scheduled electronic advertising module. The finished product shall be a main product for Infotech Net. To ensure this project is developed appropriately, developers have chosen as it outlines detailed methodology on techniques and steps to be taken.